Interactions Among the Main Characteristics of Open Building Systems - Mostafa Hosseini; Izni Syahrizal Ibrahim; Hamed Rahnama; Iman Kiani; Maryam Ghasemi (Civil and Sustainable Urban Engineering, 2022)
Constant need-for-change in the construction market and social trends has resulted in the demand for more adaptable building systems. The ability to practise and accommodate change has consequently become a new necessity for buildings. Adaptability, therefore, is to be considered in both the pre-construction stage and the entire life cycle of the construction. The further civilization develops, the more we need to take advantage of the Open Building Systems (OBS) concept, introduced to the construction industry almost 70 years ago. However, conventional methods are still common due to the lack of knowledge in OBS, resistance to change, monopoly of conventional building materials manufacturing, insufficient legislation, and lack of end-user’s awareness. The ability to practise and accommodate changes has consequently become a new necessity for building construction. This research aims to address the interactions among the influential factors of OBS. The initial move was to identify and verify the significant open building influential factors in a conceptual model based on previous relevant literature. Then the second step was to find the interactions between the variables through the Decision-Making Trial and Evaluation Laboratory (DEMATEL) technique. The results indicate that one of the most significant and main factors is the "Level of Independence", and the main cause factor identified was "Standardization (St)", which had a major role in the success of construction OBS performance.